Pre-Service Chemistry Teacher’s Conception About Chemistry of The Rare Earth Elements - Titen Pinasti; Ahmad Mudzakir; Hernani Hernani (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
Rare Earth Elements (REE) is an interesting chemistry topic, especially due to current technology development. However, new learning designs of REE need to be developed for Pre-service Chemistry Teachers (PCT) as it is not yet available. A good design is constructed by analyzing PCT pre-conceptions based on the technical difficulties faced by the students during teaching process. The study aims to identify PCT's pre-conceptions focusing on REE topic. We conducted this research involving 17 chemistry education students at the Universitas Pendidikan Indonesia, Bandung. Data was collected through interviews and analyzed using the Qualitative Content Analysis (QCA) method. Our results highlight that PCT had difficulties with chemistry content of REE, especially about electronic configuration, magnetic, and luminescence properties. In addition, PCT faced difficulties correlating electronic configuration's chemistry content into contexts. Based on the interview results, 88.2% of the students agree with the development learning design for undergraduate chemistry students. As a result, we conclude that technical difficulties and misconceptions about REE can be overcome by developing the learning design based on the need of the students.